Islamic Fundamentalism Since 1945: By Beverley Milton-Edwards (London and New York: Routledge, 2005. 158 pages.) (American Journal of Islam and Society, 2006)
For first-time students of the increasingly well-researched field of Islamicfundamentalism, or for those with a general interest keen to hone theirunderstanding, Beverly Milton-Edwards’ fourth book, Islamic FundamentalismSince 1945, is a good place to start. This compact book, running amere 139 pages of text, has a rather grand ambition: to describe the definingperiods in the growth of this phenomenon and introduce the main players aswell as the key debates. To a large degree, this ambition is successfully met.Milton-Edwards uses an historical linear approach, and so we begin, inchapter 1, with “a diverse tradition from past to present” that takes usquickly from the events following the Prophet’s death in 632 to the MuslimBrotherhood’s emergence in Egypt in 1928. The author regards its foundingfather, Hassan al-Banna (1906-49), in “many respects as the founding fatherof Islamic fundamentalism.” The subsequent chapters examine “TheAdvance of Secularism”; “Identity and Revivalism”; “Islam Armed”; and“Going Global: Fundamentalism and Terror.” With the penultimate chapter,“Ground Zero and Islamic Fundamentalism,” we are brought to the present.The year 1945, the end of the Second World War, marks the first dismembermentof the imperialist model and the emergence of new nation ...